Gender Differences and Influencing Factors in Specialty Choices: Findings From One Medical School in China - Yin, Kanhua; Yang, Liu; Zhang, Rui; Zheng, Difan; Wilkes, Michael S.; Lai, Yanni (Frontiers in Public Health, 2021)
Background: Gender plays a significant role in the selection of medical specialty. Few studies have been conducted to explore the impact of gender differences on specialty choosing among Chinese medical students. Methods: The specialty choices of 648 students from six consecutive classes in an eight-year MD program were collected and compared between male and female students. A total of 110 students from one graduating class were surveyed by a questionnaire covering 22 career influencing factors. Each factor has a scale of zero to three (zero = no influence, one = mild influence, two = moderate influence, and three = strong influence). Results: Statistically significant gender differences were observed in ten out of 16 specialties. Most male students limited their specialty choices to surgery (64%), internal medicine (12%), and orthopedics (12%), compared with a relatively diversified pattern in female students. For male students, the top three influencing factors were personal interest, future job prospects for the chosen specialty, and job opportunity in academic medicine. The strongest influencing factors of females were personal interest, specialty-specific knowledge and skills, and the sense of achievement. The expected salary was ranked among the top ten influencing factors in male but not in females, while the work-life balance was ranked among the top ten factors in females but not in males. Conclusion: There is a significant gender difference regarding specialty choices among Chinese medical students. Career coaching is needed to help students in their specialty choosing process.